Analysis of Development of Artificial Intelligence in the Game Industry - Sayid Adli Yakan (International Institute for Advanced Science & Technology (IIAST), 2022)
A game, sometimes known as a video game, is a form of modern technology-based game. Gaming is currently one of the major industries on the planet. Because gaming aficionados from all over the world number in the hundreds of millions, if not billions, this sector is very substantial. The game may be played on a PC, an Android device, or a game machine both offline and online. Artificial intelligence is also used in video games. Artificial Intelligence (AI) is artificial intelligence implemented on a computer system that allows players to compete against the computer in a game similar to that of other players. Artificial intelligence, often known as machine intelligence, is a mimic of human intellect that has been trained to think like humans. Artificial intelligence is a technology that uses data as knowledge in order for the intelligence created to improve and learn from prior failures. When employed by humans, artificial intelligence can be activated by human orders or by itself based on AI experience. The goal of this research was to figure out how artificial intelligence was progressing in the gaming business.